2009
DOI: 10.1143/jjap.48.04c101
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN/AlGaN Double Heterostructures on Silicon Substrates for High Breakdown Voltage Field-Effect Transistors with low On-Resistance

Abstract: AlGaN/GaN/AlGaN double heterostructure field-effect transistors (DHFET) with high breakdown voltage and low on-resistance were fabricated on silicon substrates. A linear dependency of the breakdown voltage on the buffer thickness and on the buffer Aluminium concentration was found. A breakdown voltage as high as 830 V and an on-resistance as low as 6.2 Ω·mm were obtained in devices processed on 3.7 µm buffer thickness. The gate–drain spacing was 8 µm and the devices did not have any field plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 11 publications
2
48
0
Order By: Relevance
“…The R ON values at any given L GD are normalized to its value at L GD of 1 m. Both devices showed nearly linear relationship between R ON and L GD , very similar to the data reported by Choi et al [37] and Visalli et al [38]. This is due to the increase in drain access resistance with L GD .…”
Section: B Improvement Of Current Stabilitysupporting
confidence: 89%
“…The R ON values at any given L GD are normalized to its value at L GD of 1 m. Both devices showed nearly linear relationship between R ON and L GD , very similar to the data reported by Choi et al [37] and Visalli et al [38]. This is due to the increase in drain access resistance with L GD .…”
Section: B Improvement Of Current Stabilitysupporting
confidence: 89%
“…11 where we compare the breakdown voltage of enhancement and depletion mode devices (24 nm thick top barrier) with an identical buffer structure, buffer thickness and device layout. We have shown before that the breakdown voltage of DHFET devices on Si substrates is governed by two mechanisms (6). For small gate-to-drain spacing, the breakdown occurs in the top part of the device structure and at a voltage which is proportional to this spacing.…”
Section: Resultsmentioning
confidence: 98%
“…The Al 18 Ga 82 N back barrier is very efficient in confining the electrons to the 2DEG, preventing them from overflowing into the buffer and towards the Si substrate. This is important because we have shown before that for large gate to drain gaps, the devices' breakdown behaviour is dominated by a double vertical path between the metal contacts and the Si substrate (6). Van der Pauw (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, the AlGaN buffer layer is preferred to be thick enough to improve crystalline quality of GaN on Si, resulting in the improvement of the performance of GaNbased electronic devices such as leakage current and breakdown voltage [10]. However, most studies suggested the total thickness of graded-AlGaN buffer layer is less than 1μm for crack-free GaN grown on Si [5,[11][12][13][14], because AlGaN layer with a large thickness would relax significantly and may not exert adequate compressive stress on GaN overlayer, resulting in cracking of GaN layer [11].…”
mentioning
confidence: 99%